ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Moniarsih, Winda; Ilhamsyah, Ilhamsyah; Mursalin, Mursalin (Universitas Nusa Cendana, 2024)
This research aims to test the hypothesis of Financial Ratio Analysis in Predicting Profit Growth in Banking Companies Listed on the Indonesia Stock Exchange (BEI). This research uses quantitative methods. The population in this study was 47 banking companies listed on the Indonesia Stock Exchange (BEI). The sample in this research consisted of 12 companies with data on 60 banking companies. The sampling technique uses purposive sampling with the criteria of all banking companies listed on the Indonesia Stock Exchange (BEI). The data analysis technique in the research uses the classic assumption test, which consists of the normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiole linear analysis, hypothesis testing consisting of the t test (partial) and f test (simultaneous), and the coefficient test determination (R2). The results of the t test hypothesis test concluded that partially Return On Asset (ROA) had no effect on profit, Net Profit Margin (NPM) has no effect on profit growth, Return On Equity (ROE) has a positive effect on profit growth. Meanwhile, simultaneously. Return On Asset (ROA) had no effect on the profit growth, Net Profit Margin (NPM) had no effect on profit growth, and Return On Equity (ROE) has a positive effect on profit growth. It can be concluded that there is a significant influence of the variables Return On Asset (ROA), Net Profit Margin (NPM), and Return On Equity (ROE) together on the variable profit growth. Keywords : Return On Asset (ROA); Net Profit Margin (NPM); Return On Equity (ROE); Profit Growth